2020
DOI: 10.1002/app.49680
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and EMI shielding studies of polyaniline grafted conducting nanohybrid

Abstract: Polyaniline (PANI) grafted conducting nanohybrids are successfully synthesized by emulsion graft polymerization. Maximum grafting of 644% is obtained on sepiolite at optimized concentrations and reaction conditions. The Fourier transform infrared (FT‐IR) spectra of sepiolite grafted polyaniline (MS‐g‐PANI) nanohybrid revealed the presence of stretching vibrations of C=C bonds of polyaniline at 1580 and 1490 cm−1 along with the characteristic peaks of sepiolite. Increased thermal stability of the nanohybrid is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 43 publications
6
3
0
Order By: Relevance
“…However, as expected, beyond this optimum amount of 10.95 mmol, the oxidant efficiency began to drop due to the excessive monomer amount to oxidize. Similar trends were also reported from the other researchers, as these studies agreed that too many monomers led to the reduction in polymerization yield [107][108][109][110]. The reduction was due to the incomplete conversion of aniline monomer to PANi [107] due to insufficient oxidation [110].…”
Section: Polymerization Yieldsupporting
confidence: 88%
See 1 more Smart Citation
“…However, as expected, beyond this optimum amount of 10.95 mmol, the oxidant efficiency began to drop due to the excessive monomer amount to oxidize. Similar trends were also reported from the other researchers, as these studies agreed that too many monomers led to the reduction in polymerization yield [107][108][109][110]. The reduction was due to the incomplete conversion of aniline monomer to PANi [107] due to insufficient oxidation [110].…”
Section: Polymerization Yieldsupporting
confidence: 88%
“…Similar trends were also reported from the other researchers, as these studies agreed that too many monomers led to the reduction in polymerization yield [107][108][109][110]. The reduction was due to the incomplete conversion of aniline monomer to PANi [107] due to insufficient oxidation [110]. In the case of the relationship between the acid concentration with polymerization yield, the improvement in yield was noted when the amount of acid was increased from 3.75 to 12.5 mmol.…”
Section: Polymerization Yieldsupporting
confidence: 87%
“…In another study, metal adsorption bands were observed on functional groups, especially S = O at 1580 and 1490 cm − 1 (Raza et al, 2021). Nitrogen and sulfur bonds were observed in the functionalized PU sample of this study.…”
Section: Discussionsupporting
confidence: 58%
“…Carbon-based materials, particularly carbon nanotubes , and graphene, , have been studied as hot spots in various fields. Not surprisingly, the carbon nanotube and graphene materials also exhibit outstanding electromagnetic wave absorption and shielding properties. , Conducting polymer composites [polyaniline (PANI), polypyrrole (PPy), polythiophene (PTh)] showed various excellent performances in the use of Joule heating and EMI shielding applications because of the adjustable conductivity. Besides, conducting polypyrrole can absorb the full spectrum light and convert it to thermal energy, which can be used for photothermal conversion. However, the lack of mechanical strength limits the commercial applications of the conductive polymers. , …”
Section: Introductionmentioning
confidence: 99%